2010
DOI: 10.1111/j.1365-246x.2010.04831.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper-mantle seismic structure beneath SE and Central Brazil from P- and S-wave regional traveltime tomography

Abstract: S U M M A R YWe present models for the upper-mantle velocity structure beneath SE and Central Brazil using independent tomographic inversions of P-and S-wave relative arrival-time residuals (including core phases) from teleseismic earthquakes. The events were recorded by a total of 92 stations deployed through different projects, institutions and time periods during the years 1992-2004. Our results show correlations with the main tectonic structures and reveal new anomalies not yet observed in previous works. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 57 publications
10
61
0
5
Order By: Relevance
“…2.4. Previous P-wave tomography in SE Brazil (Schimmel et al 2003;Assumpção et al 2004;Rocha et al 2011) had all shown generally higher velocities beneath the SFC and lower velocities beneath the Cretaceous igneous provinces (Iporá, Alto Paranaíba, and Serra do Mar) emplaced along the orogenic belts that fringe the craton to the south. High velocities have also been observed beneath the northern part of the Paraná basin, not in a single block, but in separate patches.…”
Section: P-wave Tomographymentioning
confidence: 96%
“…2.4. Previous P-wave tomography in SE Brazil (Schimmel et al 2003;Assumpção et al 2004;Rocha et al 2011) had all shown generally higher velocities beneath the SFC and lower velocities beneath the Cretaceous igneous provinces (Iporá, Alto Paranaíba, and Serra do Mar) emplaced along the orogenic belts that fringe the craton to the south. High velocities have also been observed beneath the northern part of the Paraná basin, not in a single block, but in separate patches.…”
Section: P-wave Tomographymentioning
confidence: 96%
“…Of particular relevance, a significant low velocity anomaly of P and S seismic waves was identified in the northeastern border of Paraná Basin, where it forms a vertical cylinder in the upper mantle. This was initially interpreted as a fossil plume [19], but later work suggested that it had a chemical rather than thermal origin [20].…”
Section: Geological Settingmentioning
confidence: 99%
“…Estudos regionais recentes envolvendo dados sismológicos (Julià et al, 2008;Rocha et al, 2011) favorecem a interpretação de Milani & Ramos (1998).…”
Section: Considerações Sobre a Evolução Da Bacia Do Paraná E Da Margeunclassified
“…Esse cenário impossibilitou a definição de um limite crustal lateral sob a Bacia do Manto Litosférico Paraná Norte como relativamente veloz Feng et al, 2004;Rocha et al, 2011;Chaves, 2014), condutivo (Minei, 2015;Padilha et al, 2015) e denso (Chaves, 2014 Quintas et al, 1999), que provavelmente aproveitaram transtracionalmente as estruturas brasilianas NE-SW, e foram impulsionados pelas diacrônicas fases compressivas da Orogenia Oclóyica, ocorridas na borda sul-ocidental do Gondwana (Milani & Ramos, 1998). Neste contexto, seria improvável a existência de uma litosfera com estrutura termal de baixa temperatura sob a Bacia do Paraná àquela época.…”
Section: Considerações Sobre a Evolução Da Bacia Do Paraná E Da Margeunclassified
See 1 more Smart Citation